Sputtering of silicon by atomic and cluster bismuth ions: An influence of projectile nuclearity and specific kinetic energy on the sputter yield. (June 2021) - Tolstogouzov, A.; Mazarov, P.; Ieshkin, A.E.; Belykh, S.F.; Korobeishchikov, N.G.; Pelenovich, V.O.; Fu, D.J.
Abstract: An influence of the specific kinetic energy E sp and nuclearity n of Bi n + ( n  = 1–4) projectiles on the sputter yield of Si was studied by means of the volume loss method. It was found that the specific sputter yield Y sp exhibited non-additive increase with an increasing of n and E sp values. As a non-additivity k -factor, the slope of the straight line approximating Y sp ( n ) dependences at the same specific energy was proposed to use. For Bi n + ( n  = 1–4) projectiles at E sp  = 10 keV at −1 the k -factor was equal to 0.41 ± 0.08. In addition, it was ascertained that the efficiency of energy transfer from projectiles to target atoms increased with an increase in the projectile nuclearity, e.g., it was 2.8 times greater for Bi3 + bombarding ions as compared with Bi + ones. Highlights: Si sputtering by Bi n + ( n  = 1–4) projectiles. Volume loss method for sputter yield measurements. Non-additive sputtering vs specific kinetic energy and nuclearity of projectiles.